TELAAH KITAB RASAIL AL-NUR OLEH SAID NURSI - Amir, Ahmad Nabil; Rahman, Tasnim Abdul (Sekolah Tinggi Ilmu Adab dan Budaya Islam Riyadul 'Ulum, 2023)
This paper discusses Said Nursi’s Qur’anic interpretation, Risalah al-Nur and its historical background and foundational role in Islamic intellectual history and its religious tradition under the repressive secular modern Turkish Republic administration. It looks into the cultural impact of its moral-spiritual teaching and its historical significance in developing and fulfilling the fundamental role of Qur’anic revelation in delivering and justifying the principal of ethics and morality, and its cosmological values in guiding the formation of higher ethical-legal and civilizational framework. The study is based on library research using historical and qualitative approaches and documentation technique. The finding shows that the Risalah al-Nur has set forth through empirical and scientific method, the conclusive truth of the Qur’an and hadith paradigm, by way of similitude and comparison, which provide basic proof of the postulates of its inimitability and miraculousness, that was vital in strengthening the belief of tawhid and in reinforcing the religious and spiritual consciousness of the people. In the context of its interpretation and historical significance, the discourse presented in the Risalah al-Nur emphatically upheld the teaching of the Qur’an and hadith and contextualize its transcendental ideals, philosophy and values to modern life.